Compressive strength and thermal conductivity of concrete containing biochar and porous aggregate - Toeng, Mengty; Saelim, Surasak; Kijjanon, Aunchana; Sumranwanich, Taweechai (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 27, 2022)
This research aims to study the compressive strength and thermal conductivity of concrete containing rice husk biochar (RB), expanded clay aggregate (CA), and a combination of both RB and CA. Effect of replacement percentage of biochar with binder and porous aggregate by coarse aggregate were investigated. Biochar was prepared by pyrolyzing in a furnace with a temperature of 550°C in steady-state for 8 hours. Water to cement binder was 0.50. The replacement percentage of biochar were 1%, 3%, and 5% by weight of the binder. The replacement of expanded clay aggregates was 50% by volume of coarse aggregate. The test results illustrated that the specimen containing 1% of biochar replacement showed the highest compressive strength as well as the optimum amount of the biochar replacement with the binder. However, the compressive strength of the concrete decreased with the presence of expanded clay aggregate. The concrete containing biochar and expanded clay aggregate improved the thermal properties when compared with controlled concrete.